Art world strategies: neoliberalism and the politics of professional practice in fine art education. (3rd April 2019) - Kenning, Dean
ABSTRACT: This paper explores how the expansion of professional practice on fine art courses in the UK could be detrimentally impacting on the critical and political ambitions of art education. I argue that the current student fees-debt regime institutes a neoliberal model of higher education with a focus on 'enterprise', directing student subjectivity towards competitive opportunity seeking market strategies. I examine the case of fine art professional practice through an analysis of two examples of expert advice directed to the would-be artist: the first which utilises a generic language of business management, recommending art students adopt an 'entrepreneurial mindset' in order to gain competitive advantage; the second which utilises the specific language of art world networking as a behavioural strategy for career success. I go on to identify problems with these strategic investor models, both at the level of contemporary art's critical values, and also with regard to whether the entrepreneurial model offers more and better opportunities overall. I propose a critical professional practice capable of transcending the 'reality' of individualist, market competition whilst addressing real world issues of work, career and finance, and conclude with a discussion of where ethical responsibility lies for fine art educators.